POLA PELAYANAN PUBLIK TERPADU STUDI PADA KANTOR PERIJINAN DAN PELAYANAN TERPADU KOTA BATU - Willy Tri Hardianto; Nanang Bagus S; Gatut Susanto (REFORMASI, 2012)
Field study to the decentralization factors indicates that: 1) decentralization and authority capacities given to Batu service unit are still limited, 2) institution has not been provided with clear esselon in administration structure, 3) the finding of service unit even results in service centralization, 4) service activity is implemented to two sections, County unit itself and organization unit authorized by the former 5) lack of support from unit of organization authorized in giving service is founded and 6) multiple positions at organization structure are also expressed. The output, as determined from 8 criteria, is used to value the service quality, among other; 1) Simplicity, 2) Clarity and Certainty, 3) Security, 4) Openness, 5) Efficiency, 6) Economy, 7) Justice and Decentralization, 8) Timing accuracy. The adjustment at 8 service types provided by Batu public service unit by separate study, provides that only From the eight of services provided by Batu service unit, only those two offices are called as good service quality provider. Most of the branch are still less in quality. Therefore, it can be summarized that the whole public service in Batu service unit still remains low or less